Planar Chiral [2.2]Paracyclophane-Based Bisoxazoline Ligands and Their Applications in Cu-Mediated N–H Insertion Reaction - Knoll, Daniel M. (Molecules, 2019)
New catalysts for important C–N bond formation are highly sought after. In this work, we demonstrate the synthesis and viability of a new class of planar chiral [2.2]paracyclophane-based bisoxazoline (BOX) ligands for the copper-catalyzed N–H insertion of α-diazocarbonyls into anilines. The reaction features a wide substrate scope and moderate to excellent yields, and delivers the valuable products at ambient conditions.